Laser speckle velocimetry for robot manufacturing - Charrett, Tom; Bandari, Yashwanth K.; Michel, Florent; Ding, Jialuo; Williams, Stewart W.; Tatam, Ralph P. (Cranfield University, 2017)
Data files associated with SPIE Optical Metrology, Munich 2017 paper: Thomas O. H. Charrett ; Yashwanth K. Bandari ; Florent Michel ; Jialuo Ding ; Stewart W. Williams ; Ralph P. Tatam; Laser speckle velocimetry for robot manufacturing . Proc. SPIE 10329, Optical Measurement Systems for Industrial Inspection X, 103291Z (June 26, 2017); doi:10.1117/12.2269989
Keywords: Laser speckle'; 'Manufacturing Robotics and Mechatronics (excl. Automotive Mechatronics)'; 'Manufacturing Engineering not elsewhere classified'; 'Photodetectors; Optical Sensors and Solar Cells'